Faktor-Faktor Yang Mempengaruhi Kebijakan Hutang Pada Perusahaan Manufaktur - Viriany, Gabriella Stephanie, (Jurnal Ekonomi, 2021)
This study aims to examine the effect of profitability, firm size, liquidity, and sales growth to the level of debt on manufacturing companies listed on Indonesia Stock Exchange. The study period is from 2017 to 2019. The data collection method was carried out with purposive sampling and selected 35 companies. The samples obtained were analysed using panel data regression with fixed effect model as the best model amongst other panel data regression models. The research indicates that profitability and firm size have a negative significant effect on debt. Meanwhile, liquidity has a negative non-significant effect on debt. Lastly, sales growth has a positive non-significant effect on debt.